UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA SMAN 2 KOTA BENGKULU MELALUI EKSTRAKULIKULER RISMA AL-ASHR - Nur Layli Hidayah (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2017)
The purpose of this study is to determine the activities and achievements of learning contained in RISMA AL ASHR, what  are the supporting and  inhibiting  factors and  know the efforts to improve  student  achievement through  extracurricular RISMA AL ASHR. This type of research  uses qualitative  descriptive  qualitative  research  method (qualitative  research). Infor- mants  of this study are 10 RISMA AL ASHR Board,  5 PAI Teachers  and  2 Pementors. This research  takes time during  March s.d June  2017.  The data  collection procedure of researcher use observation, interview and  documentation. Data analysis that researchers do is through  the stages of data  collection,  data  reduction, display data  and  conclusions.  From  the results of the research  so far it can  be concluded that  the activities of RISMA has  run entirely,  except  for 1 rabbana activities that  did not happen. What  is interesting  is that  RISMA managers and  builders  always  carry out  an  evaluation of the  implementation  of RISMA activities, this is very much related to forming students  who excel as outputs.  So that output  is a proof of the number of outstanding students  in RISMA. The prominent learning achievement in this RISMA student  in the form of academic achieve- ment and nonakademik